ALGORITMA IMAGE THINNING - Zurnawita Zurnawita; Zulharbi Suar (Elektron : Jurnal Ilmiah, 2009)
Using image thinning algorithm, various example of application is processing image to become more and more variate and helpfully for recognition process an image such as were studied by example. First, this handout will be explained some term which concerning image thinning in digital image processing, then definition from image thinning and algorithm to process image thinning at one particular digital image will be explained. In the next will be given an image thinning application which used for Extraction of Filarial Worms.